The Influence of Compensation and Work Environment on Employee Performance at the BAPPEDA (Regional Development Planning Agency) Office of Bengkulu Province - Chaterine Sianturi; Nasution Nasution (UNIVED Press, 2024)
The purpose of this study is to examine the impact of salary and work environment on employee performance in the Bengkulu Province BAPPEDA (Regional Development Planning Agency) Office. This study relied on primary data in the form of a questionnaire delivered to the research population. Employee performance is the dependent variable. Compensation and work environment are the independent factors considered. This study employs quantitative tools and a survey strategy. The research population consisted of 106 BAPPEDA personnel from Bengkulu Province. Purposive sampling was used to choose the research sample of 80 persons. With the assistance of SmartPLS, the data processing approach employs Structural Equation Modeling (SEM) analysis. The research results found that compensation and work environment have a significant effect on employee performance. This means that by providing appropriate compensation and a good work environment, employee performance at the BAPPEDA office can be improved.